Conductive polymer composition and method for stably storing conductive polymer solution

By integrating an N-vinyl carboxylic acid amide polymer with specific molecular weight characteristics into conductive polymer compositions, the stability and conductivity issues associated with long-term storage are addressed, ensuring consistent performance across temperature variations.

JP7662075B2Active Publication Date: 2025-04-15RESONAC CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024037257
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-05-16
Filing Date
2024-03-11
Publication Date
2025-04-15
Estimated Expiration
2040-05-14

AI Technical Summary

Technical Problem

Conductive polymer compositions, such as PEDOT-PSS, face challenges in maintaining dispersion stability over long-term storage due to intermolecular forces and tertiary structure formation in PSS, which can be disrupted by temperature changes, affecting conductivity.

Method used

Incorporating an N-vinyl carboxylic acid amide polymer with a weight average molecular weight between 5,000 and 1 million into the conductive polymer composition, which improves storage stability by weakening intermolecular forces and maintaining dispersibility and conductivity.

Benefits of technology

The addition of the N-vinyl carboxylic acid amide polymer significantly enhances the storage stability of conductive polymer compositions, ensuring consistent conductivity and dispersion stability across varying temperatures and storage durations.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007662075000005
    Figure 0007662075000005
  • Figure 0007662075000006
    Figure 0007662075000006
  • Figure 0007662075000001
    Figure 0007662075000001
Patent Text Reader

Abstract

To provide a conductive polymer composition having high dispersion stability in long-term storage without being influenced by temperature changes in the winter season, summer period, and etc. and a method for stably storing a conductive polymer solution.SOLUTION: A conductive polymer composition comprises at least a N-vinyl carboxylic acid amide polymer having a weight-average molecular weight within the range of 5000 or more and 1000000 or less, a conductive polymer, and a solvent. A method for stably storing a conductive polymer solution comprises adding, to the conductive polymer solution, a N-vinyl carboxylic acid amide polymer having a weight-average molecular weight within the range of 5000 or more and 1000000 or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a conductive polymer composition having high storage stability, and more particularly to a conductive polymer composition having high dispersion stability during long-term storage without being affected by temperature changes such as those in winter and summer, and a method for stably storing a conductive polymer solution. [Background technology]

[0002] Conductive polymers are widely used in electrolytes for solid electrolytic capacitors, antistatic materials for optical films, hole injection layers for organic electroluminescence (EL) and solar cells, transparent electrodes, actuators, sensors, thermoelectric conversion elements, and more.

[0003] As such a conductive polymer, the present applicant has proposed in Patent Document 1 listed below a conductive polymer composite containing a self-doped conductive polymer having a Brønsted acid group in the molecule and an N-vinylcarboxylic acid amide polymer between a pair of electrodes, at least one of which is transparent, and has proposed an electrochromic device in which this composite is interposed as an electrolyte.

[0004] Furthermore, the present applicant has proposed a conductive composition containing an aqueous solvent-soluble conductive polymer that has a π-electron conjugated system and exhibits conductivity through an electron conductivity mechanism, and an aqueous solvent-soluble resin in the following Patent Document 2. In Patent Document 2, examples are evaluated that contain poly(5-sulfoisothianaphthene-1,3-diyl) as the aqueous solvent-soluble conductive polymer and polyvinylacetamide as the aqueous solvent-soluble resin.

[0005] Among conductive polymers, poly(3,4-ethylenedioxythiophene) doped with poly(4-styrenesulfonic acid) (hereinafter also referred to as PEDOT-PSS) is one of the most commonly used conductive polymers due to its good conductivity and high optical transparency when used as a thin film.

[0006] Patent Document 3 below discloses a conductive composition consisting of PEDOT-PSS and poly-N-vinylacetamide (PNVA) as conductive polymers. Patent Document 3 discloses PEDOT-PSS prepared by adding a sulfuric acid-based oxidizing agent, 3,4-ethylenedioxythiophene (EDOT) as a polymerizable monomer, and polystyrene sulfonic acid as a dopant to an aqueous PNVA solution, followed by a polymerization reaction of EDOT. PNVA is added to improve adhesion between PEDOT / PSS particles and adhesion to the substrate. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Japanese Patent Application Publication No. 10-239715 [Patent Document 2] Japanese Patent Application Laid-Open No. 2006-77229 [Patent Document 3] Japanese Patent Application Laid-Open No. 2012-153867 [Non-patent literature]

[0008] [Non-Patent Document 1] Onishi, Kunikata, and Nakajima, "Effect of Additives on the Conductive Properties of PEDOT / PSS," Aviation Electronics Technical Report, March 2013, No. 35, pp. 1-9 Summary of the Invention [Problem to be solved by the invention]

[0009] Conductive polymers exist dispersed in a solvent, but this dispersion state is not permanent. For example, in PEDOT-PSS, the hydrophobic polymer PEDOT is dispersed in the hydrophilic PSS (Non-Patent Document 1). However, manufacturers and retailers specify that most PEDOT-PSS products should be stored at 2 to 8°C. Even under these conditions, the shelf life is often limited to 12 months after manufacture, posing a challenge as the material is prone to performance changes depending on storage conditions and duration.

[0010] Specifically, as the intermolecular forces between PSS molecules come into play, the PSS molecules gradually begin to take on a tertiary structure, making it difficult to maintain the initial dispersed state for a long period of time. It is known that the initial dispersion state is significantly disrupted, particularly when the material is stored in a cold region, cooled to a frozen state, and then re-thawed, or when the molecular movement is activated by heating, etc.

[0011] Furthermore, during the dispersion collapse or the process of PSS forming a tertiary structure, there is a high possibility that the insulating PSS layer will trap PEDOT inside, making PSS the outermost layer, which has raised concerns about maintaining conductivity.

[0012] Furthermore, in Patent Document 3, an oxidizing agent containing a sulfur component, such as sulfate or persulfate, is used in the presence of PNVA during polymerization of EDOT, resulting in a high sulfur content in the composition. Furthermore, the PNVA used during polymerization has a high viscosity and molecular weight. Furthermore, Patent Document 3 uses GE191-000, a product of the present applicant, which has a high viscosity of 500 mPa·s in a 1% by mass aqueous solution, a weight-average molecular weight of 4,000,000, and contains sulfur derived from chain transfer agents, which is undesirable in semiconductors. Therefore, the conductive composition described in Patent Document 3, which uses such PNVA, has the problem of being difficult to use in semiconductors and has high viscosity, making it difficult to use as a dispersant. [Means for solving the problem]

[0013] Under these circumstances, the present inventors conducted extensive research and found that the molecular weight of the N-vinylcarboxylic acid amide polymer significantly affects the long-term storage stability of a conductive polymer composition. They also found that adding a specific N-vinylcarboxylic acid amide polymer to a conductive polymer composition significantly improves storage stability, leading to the completion of the present invention.

[0014] That is, the present invention is configured as follows. [1] A conductive polymer composition comprising at least an N-vinylcarboxylic acid amide polymer having a weight-average molecular weight in the range of 5,000 to 1,000,000, a conductive polymer, and a solvent. [2] The conductive polymer composition according to [1], characterized in that the solid content of the N-vinylcarboxylic acid amide polymer is 10 parts by mass or more and 200 parts by mass or less, based on 100 parts by mass of the solid content of the conductive polymer. [3] The conductive polymer composition according to [1] or [2], wherein the solid content concentration of the N-vinylcarboxylic acid amide polymer in the conductive polymer composition is 0.3 mass % or more and 10 mass % or less. [4] The conductive polymer composition according to any one of [1] to [3], wherein the N-vinylcarboxylic acid amide polymer is an N-vinylacetamide polymer. [5] The conductive polymer composition according to any one of [1] to [4], wherein the conductive polymer is poly(3,4-ethylenedioxythiophene) doped with poly(4-styrenesulfonic acid) (hereinafter referred to as PEDOT-PSS). [6] The conductive polymer composition according to any one of [1] to [5], wherein the solvent is water. [7] The conductive polymer composition according to any one of [1] to [6], wherein the viscosity of the conductive polymer composition at 20°C is 10 mPa·s or more and 400 mPa·s or less. [8] The conductive polymer composition according to any one of [1] to [7], wherein the sulfur concentration in the solid content of the N-vinylcarboxylic acid amide polymer is 3000 mass ppm or less. [9] The conductive polymer composition according to any one of [1] to [8], wherein the N-vinylcarboxylic acid amide polymer is produced by polymerizing N-vinylcarboxylic acid amide in the presence of a chain transfer agent not containing a sulfur atom, or without using a chain transfer agent.

[10] A method for stably storing a conductive polymer solution, comprising adding an N-vinylcarboxylic acid amide polymer having a weight-average molecular weight in the range of 5,000 to 1,000,000 to the conductive polymer solution.

[11] The method for stably storing a conductive polymer solution according to

[10] , wherein the conductive polymer solution contains at least PEDOT-PSS and water.

[12] The method for stably storing a conductive polymer solution according to

[10] or

[11] , wherein the N-vinylcarboxylic acid amide polymer is an N-vinylacetamide polymer.

[13] The method for stably storing a conductive polymer solution according to any one of

[10] to

[12] , wherein the N-vinylcarboxylic acid amide polymer is produced by polymerizing N-vinylcarboxylic acid amide in the presence of a chain transfer agent that does not contain a sulfur atom or without using a chain transfer agent.

[14] The method for stably storing a conductive polymer solution according to any one of

[10] to

[13] , wherein the sulfur concentration in the solid content of the N-vinylcarboxylic acid amide polymer is 3000 mass ppm or less. [Effects of the Invention]

[0015] According to the present invention, the storage stability is significantly improved by adding a specific N-vinylcarboxylic acid amide polymer to a conductive polymer solution. The present inventors believe that adding the N-vinylcarboxylic acid amide polymer used in the present invention to, for example, PEDOT-PSS can weaken the intermolecular forces between PEDOT and PSS or between PSS and PEDOT complexes, thereby preventing the formation of a tertiary structure in PSS alone. It is known that PEDOT-PSS forms a higher-order structure, which contributes to its cohesion.

[0016] Furthermore, the amphiphilicity of the N-vinylcarboxylic acid amide polymer ensures or improves the aqueous dispersibility of PEDOT, thereby enabling it to maintain its conductive properties for a long period of time. Furthermore, while the PEDOT-PSS solution is strongly acidic for stability, PNVA, with its excellent acid resistance, does not deteriorate even in such a strong acidic solution. Furthermore, its excellent heat resistance allows it to maintain its effectiveness even when heated during the formation of conductive polymer films.

[0017] Since sulfur atoms are likely to affect the movement of electrons, in the present invention, by using an N-vinylcarboxylic acid amide polymer in which the sulfur content is reduced to within a predetermined range, high conductivity can be maintained more stably.

[0018] In fact, N-vinylcarboxylic acid amide polymers polymerized using a chain transfer agent containing SH groups or N-vinylcarboxylic acid amide polymers containing many sulfur atoms may discolor other materials in accelerated tests.

[0019] Furthermore, the N-vinylcarboxylic acid amide polymer of the present invention has sufficient wettability, and can also improve the affinity of the polymer to glass substrates, metals, etc. when forming a conductive polymer film.

[0020] Furthermore, since the N-vinylcarboxylic acid amide polymer itself has excellent transparency, it can be used in applications where transparency is required, and antistatic effects can also be expected. [Brief explanation of the drawings]

[0021] [Figure 1] 1 shows the particle size distribution of the conductive polymer composition after freezing and heating tests evaluated in Example 1. [Figure 2] 1 shows the particle size distribution of the conductive polymer composition after freezing and heating tests, evaluated in Comparative Example 1. DETAILED DESCRIPTION OF THE INVENTION

[0022] Hereinafter, the present invention will be specifically described. The composition of the present invention is of course not limited to these. The conductive polymer composition of the present invention at least contains an N-vinylcarboxamide polymer, a conductive polymer, and a solvent.

[0023] <N-vinylcarboxamide polymer> The N-vinylcarboxamide polymer of the present invention is obtained by polymerizing an N-vinylcarboxamide monomer represented by formula (1).

[0024] [Chemical formula] (In general formula (1), R 1 is any one selected from the group consisting of a hydrogen atom and a hydrocarbon group having 1 to 6 carbon atoms. R 2 represents a hydrogen atom or a hydrocarbon group having 1 to 6 carbon atoms. R 1 may form a ring structure with NR 2 ).

[0025] Specific examples of the N-vinylcarboxamide include N-vinylformamide, N-vinylacetamide, N-vinylpropionamide, N-vinylbenzamide, N-vinyl-N-methylformamide, N-vinyl-N-ethylformamide, N-vinyl-N-methylacetamide, N-vinyl-N-ethylacetamide, N-vinylpyrrolidone, and the like. Among these, N-vinylacetamide is particularly preferable in view of the balance between the hydrophilicity and hydrophobicity of the polymer. The N-vinylcarboxamide may be used alone or in combination of two or more.

[0026] The N-vinylcarboxylic acid amide polymer is preferably a homopolymer of only N-vinylcarboxylic acid amide. On the other hand, in addition to N-vinylcarboxylic acid amide, it may contain a monomer copolymerizable with N-vinylcarboxylic acid amide (hereinafter, sometimes referred to as "other monomer"). The other monomer is at least one monomer selected from the group consisting of unsaturated carboxylic acid monomers, salts of unsaturated carboxylic acid monomers, unsaturated carboxylic acid ester monomers, vinyl ester monomers, and unsaturated nitrile monomers. Among these, (meth)acrylic acid and its salts are more preferred, and sodium acrylate is even more preferred. In this specification, "(meth)acrylic acid" refers to acrylic acid and methacrylic acid.

[0027] The N-vinylcarboxylic acid amide polymer preferably has a molar ratio of the other N-vinylacetamide-derived structural units to the N-vinylcarboxylic acid amide-derived structural units of less than 0.250, where the molar ratio of the N-vinylcarboxylic acid amide-derived structural units is taken as 1.00. The N-vinylacetamide copolymer more preferably has a molar ratio of the above structural units of 0.150 or less, and even more preferably 0.

[0028] A polymerization initiator may be used when polymerizing the N-vinylcarboxylic acid amide monomer. The polymerization initiator may be any initiator commonly used in the radical polymerization of vinyl compounds, without limitation. Examples of the polymerization initiator include redox-based polymerization initiators, azo compound-based polymerization initiators, and peroxide-based polymerization initiators.

[0029] These may be used alone or in combination of two or more. Examples of redox polymerization initiators are not particularly limited as long as they involve the addition of a peroxide and a reducing agent, but those that do not contain sulfur atoms are preferred because they can cause discoloration. Peroxides are compounds that contain oxygen atoms bonded together, and hydrogen peroxide derivatives such as sodium peroxide and barium peroxide are preferred. Furthermore, reducing agents that contain divalent iron ions, amines, and hydrogen peroxide-ferrous chloride reducing agents are preferred, with those that do not contain sulfur atoms being even more preferred.

[0030] Examples of peroxide polymerization initiators include persulfates of sodium, potassium, ammonium, etc., and organic peroxides such as benzoyl peroxide, lauroyl peroxide, caproyl peroxide, t-butyl peroctoate, and diacetyl peroxide.

[0031] Examples of the azo compound polymerization initiator include 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), dimethyl-2,2'-azobis(isobutyrate), dimethyl-2,2'-azobis(2-methylbutyrate), dimethyl-2,2'-azobis(2,4-dimethylpentanoate), 2,2'-azobis(2-amidinopropane) dihydrochloride, 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine]n hydrate, 2,2'-azobis[2-[N-(2-carboxyethyl)amidino]propane}n hydrate, and 2,2'-azobis(2-methylpropionate) dimethyl azo compounds.

[0032] Since it is preferable to use water as the solvent, among the above polymerization initiators, a water-soluble polymerization initiator is preferable. In addition, in consideration of the influence of residues on the polymer, it is most preferable to use halogen-free 2,2'-azobis[N-(carboxyethyl)-2-methylpropionamidine]tetrahydrate (trade name: azo compound polymerization initiator VA-057 manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.).

[0033] The polymerization initiator is preferably used after being dissolved in water such as ion-exchanged water. These radical polymerization initiators may be used in combination, and polymerization is also possible using a combination of a redox polymerization initiator and a water-soluble azo compound polymerization initiator. As the redox polymerization initiator, it is preferable to use a hydrogen peroxide derivative and an amine, and it is more preferable to use 2,2'-azobis(2-amidinopropane) dihydrochloride as the water-soluble azo compound polymerization initiator.

[0034] The amount of radical polymerization initiator used, relative to 100 parts by mass of the total amount of all monomers, is preferably 0.05 to 8.0 parts by mass, more preferably 0.5 to 6.0 parts by mass, and even more preferably 1.0 to 4.0 parts by mass, in the case of an azo compound polymerization initiator. In the case of a redox polymerization initiator, the amount is preferably 0.001 to 0.03 parts by mass, more preferably 0.003 to 0.01 parts by mass, and even more preferably 0.004 to 0.009 parts by mass, relative to 100 parts by mass of the total amount of all monomers. When the amount of radical polymerization initiator used is within the above range, both the polymerization rate and the molecular weight of the copolymer tend to be favorable.

[0035] When polymerizing the N-vinylcarboxylic acid amide monomer, molecular weight adjustment may be performed using a chain transfer agent. The chain transfer agent is not particularly limited as long as it is soluble in the above-mentioned monomer and solvent. Examples include alkyl thiols such as dodecyl mercaptan and heptyl mercaptan, water-soluble thiols having a polar group such as 3-mercaptopropionic acid (BMPA), and oil-based radical inhibitors such as α-styrene dimer. Other possible agents include secondary alcohols such as isopropyl alcohol; phosphorous acid, hypophosphorous acid and its salts (sodium hypophosphite, potassium hypophosphite, etc.); and carbon tetrachloride.

[0036] To polymerize an N-vinylcarboxylic acid amide polymer having a low molecular weight and low viscosity, it is preferable not to use a chain transfer agent. However, if a chain transfer agent is used, it is preferable to use one that does not contain sulfur atoms, such as thiol. It is believed that the sulfur atoms in the chain transfer agent affect the electron transfer of the conductive polymer. Furthermore, in order to reduce the sulfur concentration, it is preferable not to use highly water-soluble sulfurous acid or sulfite salts, which are used as polymerization initiators or chain transfer agents. The presence of sulfur atoms can cause coloration and may impair dispersibility during long-term storage.

[0037] On the other hand, chain transfer agents and polymerization initiators containing sulfur components can also be used as long as the concentration of sulfur atoms is considered, as described below. In this case, thiol compounds such as 2-hydroxyethanethiol, 3-mercaptopropionic acid, dodecanethiol, thioacetic acid, and 3-mercapto-1,2-propanediol are preferred.

[0038] The concentration of sulfur atoms in the N-vinylcarboxylic acid amide polymer is preferably 0 to 6000 ppm by mass, more preferably 0 to 3000 ppm by mass, and even more preferably 0 to 500 ppm by mass, based on the total amount of all monomers.

[0039] Aqueous solutions containing N-vinylcarboxylic acid amide polymers have a high refractive index and are stable even under redox conditions. Therefore, even when mixed with conductive polymers, they are less likely to change due to heat or aging, and as a result, transparency can be maintained.

[0040] The weight average molecular weight of the N-vinylcarboxylic acid amide polymer is 5,000 or more and 1,000,000 or less, preferably 10,000 or more and 500,000 or less, more preferably 20,000 or more and 300,000 or less, and even more preferably 30,000 or more and 100,000 or less, so as not to increase the viscosity of the conductive polymer composition.

[0041] The viscosity of a 5% by mass aqueous solution of the N-vinylcarboxylic acid amide polymer at 20°C is 10 mPa·s or more and 5000 mPa·s or less, more preferably 20 mPa·s or more and 2000 mPa·s or less, and even more preferably 30 mPa·s or more and 100 mPa·s or less. A viscosity of 10 mPa·s or more is preferable because the molecular weight required for dispersibility can be obtained. A viscosity of 2000 mPa·s or less is preferable because it does not increase viscosity and therefore makes it possible to impart dispersion stability without changing the liquid properties of PEDOT-PSS.

[0042] When the N-vinylcarboxylic acid amide polymer contains water as a solvent, the pH of the conductive polymer is usually in the range of 4-10. When the N-vinylcarboxylic acid amide contains a solvent, the solids concentration of the N-vinylcarboxylic acid amide is preferably 1% by mass to 40% by mass, more preferably 2% by mass to 20% by mass, and even more preferably 3% by mass to 12% by mass. If the N-vinylcarboxylic acid amide polymer is 1% by mass to 40% by mass, handling of the conductive polymer composition becomes easy, which is preferable.

[0043] <Conductive polymer> As the conductive polymer, a combination of an anion-doped conductive polymer and a dopant is preferred.

[0044] The anion-doped conductive polymer is preferably at least one selected from the group consisting of aliphatic conjugated polyacetylene, aromatic conjugated poly(p-phenylene), mixed conjugated poly(p-1,4-phenylenevinylene), heterocyclic conjugated polypyrrole, polythiophene, heteroatom-containing conjugated polyaniline, and multi-chain conjugated polyacene (virtual molecule). Among these, poly(3,4-ethylenedioxythiophene) (hereinafter also referred to as PEDOT) is particularly preferred.

[0045] The dopant may be any dopant that has the function of donating and receiving electrons, but a dopant having a sulfonic acid group is preferred in order to maintain the electrical conductivity of the coating film, and at least one selected from polystyrene sulfonic acid, p-toluenesulfonic acid, dodecylbenzenesulfonic acid, 1,5-anthraquinonedisulfonic acid, 2,6-anthraquinonedisulfonic acid, anthraquinonesulfonic acid, 4-hydroxybenzenesulfonic acid, methylsulfonic acid, and nitrobenzenesulfonic acid is preferred. Of these, poly(4-styrenesulfonic acid) (hereinafter also referred to as PSS) is particularly preferred.

[0046] Of these, the most preferred combination is poly(3,4-ethylenedioxythiophene) doped with poly(4-styrenesulfonic acid) (hereinafter also referred to as PEDOT-PSS). The relationship between the conductive polymer and the N-vinylcarboxylic acid amide polymer is such that, relative to 100 parts by mass of the solid content of the conductive polymer, the solid content of the N-vinylcarboxylic acid amide polymer is preferably in the range of 10 parts by mass or more and 200 parts by mass or less, more preferably 20 parts by mass or more and 140 parts by mass or less, and even more preferably 30 parts by mass or more and 70 parts by mass or less. When the content is in such a ratio, deterioration of the conductive polymer over time can be sufficiently suppressed, which is preferable.

[0047] <Solvent> The solvent used in the conductive polymer composition of the present invention is preferably a polar solvent such as water or alcohol, and particularly preferably water, of which water is particularly preferred from the viewpoint of dispersibility of the conductive polymer and the N-vinylcarboxylic acid amide polymer.

[0048] <Composition> The conductive polymer composition preferably has a solid content of 0.1 to 30.0 mass%, more preferably 0.5 to 20.0 mass%, and even more preferably 1.0 to 5.0 mass%, of the N-vinylcarboxylic acid amide polymer and the conductive polymer, when the total weight of the composition is 100 mass%.

[0049] The content of the N-vinylcarboxylic acid amide polymer in the solid content is preferably in the range of 10 to 80 mass %, more preferably 20 to 60 mass %, and even more preferably 30 to 40 mass %.

[0050] The solid content concentration of the N-vinylcarboxylic acid amide polymer in the conductive polymer composition is preferably 0.3 mass % or more and 10 mass % or less, more preferably 0.5 mass % or more and 5 mass % or less, and even more preferably 0.7 mass % or more and 3 mass % or less.

[0051] When the content is within such a ratio, the change over time of the conductive polymer can be sufficiently suppressed, and the viscosity of the conductive polymer composition does not increase, which is preferable. The N-vinylcarboxylic acid amide polymer has the effect of dispersing and stabilizing the conductive polymer by itself, and in this case, it is used in the form of a solution or dispersion in which it is dissolved in a solvent.

[0052] The viscosity of the conductive polymer composition is preferably 10 mPa·s or more and 400 mPa·s or less, more preferably 20 mPa·s or more and 300 mPa·s or less, and even more preferably 30 mPa·s or more and 200 mPa·s or less. If the viscosity is 10 mPa·s or more, the composition contains a polymer with the molecular weight required for dispersibility. If the viscosity is 400 mPa·s or less, the composition does not thicken, which is preferable because it is possible to impart dispersion stability without changing the liquid properties of PEDOT-PSS.

[0053] The conductive polymer to be added is not particularly limited, and examples thereof include those mentioned above, with PEDOT and PSS being preferred. According to the present invention, there is also provided a method for stably storing a conductive polymer solution by adding the N-vinylcarboxylic acid amide polymer or a conductive polymer dispersion stabilizer containing the same to the conductive polymer solution. [Example]

[0054] The present invention will be described below with reference to examples, but the present invention is not to be construed as being limited to these examples. <Solid content concentration> The solid content concentration was calculated as follows. Approximately 3.0 g of a sample (N-vinylcarboxylic acid amide polymer or conductive polymer composition) was taken, placed on an aluminum cup, and spread evenly and smoothly over the bottom of the aluminum cup with a medicine spoon. The sample was then dried by heating at 140°C for 90 minutes on a thermobalance (PM460, manufactured by Mettler-Toledo K.K.), and the mass was measured after cooling. The solids concentration was calculated using the following formula. Solid content concentration (mass%) = 100 × (M3-M1) ÷ (M2-M1) M1: Mass of aluminum cup (g) M2: Sample mass before drying + aluminum cup mass (g) M3: Sample mass after drying + aluminum cup mass (g)

[0055] <Viscosity> When measuring the viscosity of an aqueous solution of an N-vinylcarboxylic acid amide polymer, place the N-vinylcarboxylic acid amide polymer in a 300 ml tall beaker and dilute it with ion-exchanged water so that the solid content concentration becomes 5% by mass. When measuring the viscosity of the conductive polymer composition, measure it without dilution. Leave it standing in a thermostatic bath at 20 °C for 12 hours or more until there are no internal bubbles. Then, place the beaker in a thermostatic water bath adjusted to 20 °C and confirm with a thermometer that the test body temperature is 20 ± 0.5 °C, and measure the viscosity under the following conditions using a B-type viscometer shown in JIS K-7117-1-1999. Record the viscosity 10 minutes after installing the viscometer. Viscometer: DVE (Brookfield) viscometer, HA type Spindle: No. 6 spindle Rotation speed: 50 rpm Temperature: 20 °C

[0056] <Particle size> Using a laser diffraction / scattering type particle size distribution measuring device (manufactured by Horiba, Ltd., Partica mini LA-350), the median diameter based on volume distribution (hereinafter sometimes referred to as d 50 ), and the volume average diameter based on volume distribution were measured.

[0057] <Measurement of absolute molecular weight of standard N-vinylacetamide polymer for GPC calibration curve preparation> N-vinylacetamide homopolymers in each molecular weight range were dissolved in an eluent and left standing for 20 hours. The solid content concentration in this solution is 0.05% by mass. This was filtered through a 0.45 μm membrane filter, and the absolute molecular weight at the peak position of the filtrate was measured using GPC-MALS (multi-angle light scattering detector). GPC: Shodex (registered trademark) SYSTEM21 manufactured by Showa Denko K.K. Column: Shodex (registered trademark) LB-80 manufactured by Showa Denko K.K. Column temperature: 40 °C Eluent: 0.1 mol / L NaH2PO4 + 0.1 mol / L Na2HPO4 Flow rate: 0.64mL / min Sample injection volume: 100 μL MALS detector: Wyatt Technology Corporation, DAWN (registered trademark) DSP Laser wavelength: 633nm Multi-angle fit method: Berry method

[0058] <Weight average molecular weight> The N-vinylacetamide polymer was diluted with distilled water to a solid content concentration of 0.1% by mass, and the weight average molecular weight Mw was measured by GPC (gel permeation chromatography) under the following conditions.

[0059] The weight average molecular weight in this measurement was determined using a calibration curve prepared from the results of absolute molecular weight measurements of N-vinylacetamide polymers in each molecular weight range using a multi-angle light scattering detector. Detector (RI): SHODEX (registered trademark) RI-201H manufactured by Showa Denko K.K. Pump: Shimadzu Corporation LC-20AD Column oven: SHODEX (registered trademark) AO-30C manufactured by Showa Denko K.K. Analysis equipment: System Instruments SIC 480II Data Station Column: SHODEX (registered trademark) SB806 (2 columns) manufactured by Showa Denko K.K. Eluent: distilled water / 2-propanol = 8 / 2 (mass ratio) Flow rate: 0.7ml / min

[0060] <Suction filtration test> Using a membrane filter with a pore size of 0.45 μm and a funnel, 10 ml of the conductive polymer composition was filtered under reduced pressure, and the number of aggregates formed on the filter paper was counted visually.

[0061] <Discoloration> The change in color of the conductive polymer composition before and after the storage stability test was confirmed by visual observation.

[0062] [Manufacturing Example 1] A five-neck, 1 L separable flask was equipped with a nitrogen gas inlet tube, a stirrer, two solvent droppers, and a thermometer. 250 g of ion-exchanged water adjusted to pH 7.0 with triethanolamine was added to the separable flask. The solution was stirred at 99°C for 120 minutes while nitrogen gas was purged. 107 g of N-vinylacetamide (Showa Denko K.K.) and 140 g of ion-exchanged water adjusted to pH 7.0 with triethanolamine were added to the solvent dropper and dissolved. In a separate solvent dropper, 3.2 g of the polymerization initiator 2,2'-azobis[N-(carboxyethyl)-2-methylpropionamidine]tetrahydrate (VA-057) (Fujifilm Wako Pure Chemical Industries, Ltd.) was dispersed in 40 g of ion-exchanged water adjusted to pH 7.0 with triethanolamine. The separable flask was maintained at 99°C, and the solution and dispersion were each added dropwise from two solvent droppers to the separable flask over a period of 2 hours using pumps. After 15 minutes of holding, 0.5 g of VA-057 was dispersed in 35 g of ion-exchanged water adjusted to pH 7.0 with triethanolamine, and the resulting solution was added dropwise over a period of 5 minutes using the solvent dropper. The polymerization initiator was 3.4% by mass relative to the monomer. After 45 minutes, 488 g of ion-exchanged water adjusted to pH 7.0 with triethanolamine was added and cooled. The mixture was then maintained at 50°C for 1 hour. A sample was taken, and the residual N-vinylacetamide monomer concentration was confirmed to be 1,000 ppm by mass or less, marking the end of the reaction. The weight-average molecular weight of the resulting N-vinylcarboxylic acid amide polymer was 80,000, and the viscosity of a 5% solids aqueous solution was 80 mPa·S.

[0063] [Manufacturing Example 2] The same procedure as in Production Example 1 was repeated, except that 1.6 g of 3-mercapto-1,2-propanediol (Asahi Chemical Industry Co., Ltd.) as a chain transfer agent was added when 107 g of N-vinylacetamide (Showa Denko K.K.) and 140 g of ion-exchanged water adjusted to pH 7.0 with triethanolamine were added. The weight-average molecular weight of the N-vinylcarboxylic acid amide polymer was 59,000, and the viscosity of an aqueous solution with a solids concentration of 5% by mass was 78 mPa·S. The sulfur concentration in the solid content of the N-vinylcarboxylic acid amide polymer was 4500 ppm by mass.

[0064] [Example 1] In a 50 ml beaker, 2.0 g of the N-vinylacetamide polymer aqueous solution produced in Production Example 1 was added to 20 g of a solution obtained by diluting a 4.0 mass % PEDOT-PSS dispersion solution twice by mass with ion-exchanged water, and the mixture was stirred for 5 minutes with a magnetic stirrer (400 rpm) to obtain a conductive polymer composition.

[0065] [Example 2] The same procedures as in Example 1 were carried out, except that the sulfur-containing N-vinylacetamide polymer produced in Production Example 2 was used as the N-vinylacetamide polymer.

[0066] [Comparative Example 1] The procedure was the same as in Example 1, except that 2.0 g of water was added instead of the N-vinylacetamide polymer aqueous solution. The viscosity of the water was 20.1 mPa·S.

[0067] Comparative Example 2 The same procedures as in Example 1 were carried out, except that a solution of 11 g of N-vinylpyrrolidone polymer (weight average molecular weight: 40,000, viscosity of an aqueous solution with a solid content of 5% by mass: 56.6 mPa S) dissolved in 99 g of ion-exchanged water was used instead of the N-vinylacetamide polymer aqueous solution.

[0068] Comparative Example 3 The same procedure as in Example 1 was carried out, except that the N-vinylacetamide polymer used was one prepared by dissolving 11 g of powdered N-vinylacetamide polymer (GE191-000, manufactured by Showa Denko KK) in 99 g of ion-exchanged water.

[0069] [Example 3] In a 50 ml beaker, 2.0 g of the N-vinylacetamide polymer aqueous solution produced in Production Example 1 was added to 25 g of a solution obtained by diluting a 4.0 mass % PEDOT-PSS dispersion solution twice by mass with ion-exchanged water, and the mixture was stirred for 5 minutes with a magnetic stirrer (400 rpm) to obtain a conductive polymer composition.

[0070] [Example 4] In a 50 ml beaker, 1.0 g of the N-vinylacetamide polymer aqueous solution produced in Production Example 1 was added to 25 g of a solution obtained by diluting a 4.0 mass % PEDOT-PSS dispersion solution twice by mass with ion-exchanged water, and the mixture was stirred for 5 minutes with a magnetic stirrer (400 rpm) to obtain a conductive polymer composition.

[0071] Comparative Example 4 The same procedure as in Example 3 was carried out except that 1.0 g of water was added instead of the aqueous N-vinylacetamide polymer solution.

[0072] [Example 5] 25 g of a 4.0 mass % PEDOT-PSS dispersion and 1.0 g of the N-vinylacetamide polymer aqueous solution produced in Production Example 1 were added to a 50 ml beaker and stirred for 5 minutes with a magnetic stirrer (400 rpm) to obtain a conductive polymer composition.

[0073] Comparative Example 5 The same procedure as in Example 5 was carried out except that 1.0 g of water was added instead of the aqueous N-vinylacetamide polymer solution.

[0074] The reagents used were as follows: PEDOT-PSS: Sigma-Aldrich Japan, 3.0-4.0% aqueous solution, high conductivity grade N-vinylpyrrolidone polymer: K 30 (weight average molecular weight 40,000), manufactured by Tokyo Chemical Industry Co., Ltd. N-vinylacetamide polymer (powder): GE191-000, manufactured by Showa Denko K.K.

[0075] <Storage stability evaluation> Storage stability was evaluated for Examples 1 and 2 and Comparative Examples 1 and 2. Comparative Example 3 was not evaluated because the viscosity of N-vinylacetamide was too high and was therefore unsuitable. 10 g of the prepared conductive polymer composition was placed in a 20 ml glass test tube with a lid and sealed, and treated under the following treatment conditions to prepare a sample. i) Freezing -15℃ x 6 hours The samples were frozen in a freezer (Nippon Freezer Co., Ltd., KD-3142) at -15°C for 6 hours, and then the sample temperature was raised to 30°C over 2 hours. ii) Heating 80℃×48Hr Another sample was kept in an autoclave (Yamato Scientific Co., Ltd., DN-41) at 80°C for 48 hours, and then the sample temperature was lowered to 30°C over two hours. iii) Heating 97℃×72Hr Another sample was kept in an autoclave (Yamato Scientific Co., Ltd., DN-41) at 97°C for 72 hours, and then the sample temperature was lowered to 30°C over two hours.

[0076] The heating and freezing were carried out as accelerated tests. Each sample was subjected to particle size measurement, suction filtration test, and visual inspection to check for discoloration. A score of 0 aggregates was given as ○, 1 to 3 as △, and 4 or more as ×. No discoloration was given as ○, slight discoloration as △, and significant discoloration as ×. As an overall judgment, both ○ were given as ○, ○△ and △△ as △, and anything else was given as ×.

[0077] Examples 3 to 5 and Comparative Examples 4 and 5 were subjected to a storage stability test for a longer period than Examples 1 and 2 and Comparative Examples 1 and 2, and were evaluated by measuring viscosity changes and particle diameters. In Examples 3 to 5 and Comparative Examples 4 and 5, 10 g of the prepared conductive polymer composition was placed in a 20 ml glass test tube with a lid and sealed, and samples were prepared by treating under the following conditions: The temperatures shown in Tables 2 and 3 were maintained in an autoclave (Yamato Scientific Co., Ltd., DN-41) for the times shown in Tables 2 and 3, and then the sample temperature was raised to 30°C over two hours. The results are shown in Tables 1 to 3, respectively.

[0078] [Table 1]

[0079] FIG. 1 shows the particle size distribution of the conductive polymer composition of Example 1, and FIG. 2 shows the particle size distribution of Comparative Example 1 after the freezing and heating tests.

[0080] In Example 1, there was no discoloration, the number of aggregates was small, and the particle size was small so that the product could be used. In Example 2, the color changed to blue, suggesting that the presence of sulfur compounds derived from the chain transfer agent had changed the dispersion state of the conductive polymer; however, the particle size was small and the number of aggregates was small, so the sample was usable.

[0081] From Table 1 and Figures 1 and 2, it was confirmed that in Comparative Examples 1 and 2, in which PNVA was not added, the particle size was larger than in Example 1, and aggregation had progressed. Furthermore, it can be seen that in the aggregation test, Comparative Examples 1 and 2 produced more aggregates than Example 1.

[0082] In Comparative Example 2, the color changed to blue, suggesting that the aggregation state also changed. In the case of the N-vinylpyrrolidone polymer, this suggests that the polymer changed due to the acidic state of the conductive polymer.

[0083] In Comparative Example 3, a conductive polymer composition containing 1 mass % of N-vinylcarboxylic acid amide polymer was prepared under the same conditions as in Patent Document 3. However, the viscosity was as high as 500 mPa s, making it difficult to handle as a conductive polymer composition, such as during transportation.

[0084] [Table 2]

[0085] In Comparative Example 4, in which PNVA was not added, the particle size was larger than in Examples 3 and 4, and it was confirmed that aggregation had progressed.

[0086] [Table 3]

[0087] In Example 5 and Comparative Example 5, which had a higher PEDOT-PSS concentration than the other Examples and Comparative Examples, an increase in viscosity was confirmed during the degradation test. This is presumed to be due to interactions between PEDOT-PSS molecules.

[0088] However, in Comparative Example 5, in which PNVA was not added, the particle size was larger than in Example 5, and it was confirmed that aggregation had progressed.

Claims

1. A method for stably storing a conductive polymer solution, comprising adding to the conductive polymer solution an N-vinylacetamide homopolymer having a weight average molecular weight in the range of 5,000 to 1,000,000 and a sulfur concentration in the solid content of 3,000 ppm by mass or less.

2. 2. The method for stably storing a conductive polymer solution according to claim 1, wherein the conductive polymer solution contains at least PEDOT-PSS and water.

3. 3. The method for stably storing a conductive polymer solution according to claim 1, wherein the N-vinylacetamide homopolymer is produced by polymerizing N-vinylacetamide in the presence of a chain transfer agent not containing a sulfur atom or without using a chain transfer agent.

Citation Information

Patent Citations

  • N-vinyl amide polymer and production thereof

    JP1998060047A

  • Electrochromic element

    JP1998239715A

  • N-vinylcarboxylic acid amide-based polymer and its production

    JP1999322849A

  • Nonaqueous battery, paste for electrode used in battery and electrode

    JP2002251999A

  • Conductive composition and application thereof

    JP2006077229A